2015
DOI: 10.1177/0194599814567874
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation after Middle Fossa Vestibular Schwannoma Removal

Abstract: For patients with VS in whom serviceable hearing is preserved following the MCF approach, the long-term hearing outcome remains durable in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the long-term analysis from the large Danish cohort of observed patients (86), of the 178 patients with AAO-HNS Class A hearing at the start of observation, Class A hearing was preserved in 46% at 10 years. Quist et al (94) reported five-year follow-up results of patients treated by middle cranial fossa surgical approach. Of the 49 patients with AAO-HNS Class A or B hearing preoperatively, 55% maintained Class A/B hearing immediately post-operative.…”
Section: Discussionmentioning
confidence: 99%
“…In the long-term analysis from the large Danish cohort of observed patients (86), of the 178 patients with AAO-HNS Class A hearing at the start of observation, Class A hearing was preserved in 46% at 10 years. Quist et al (94) reported five-year follow-up results of patients treated by middle cranial fossa surgical approach. Of the 49 patients with AAO-HNS Class A or B hearing preoperatively, 55% maintained Class A/B hearing immediately post-operative.…”
Section: Discussionmentioning
confidence: 99%
“…The durability of hearing preservation should be reported as well because continued reduction over time in serviceable hearing after GKS is often reported [ 1 , 4 , 27 ], with an acceleration of the decrease between years 5 and 10 [ 8 ], whereas hearing preservation after microsurgery is thought to be more durable [ 5 ]. Moving from class A to class B is still beneficial for the patients because the patients with post-GKS serviceable hearing may benefit from a unilateral hearing aid on the tumor side, whereas CROS or BICROS are more indicated for patients with post-GKS classes C and D.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing outcomes have been reported as more durable after surgery than after GKS [ 4 , 5 ] with variable hearing preservation rates. Some authors have reported good outcomes with speech discrimination over 50% [ 6 , 7 ]; others have observed poor long-term results with speech discrimination at 10 years under 3% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1) is similar to previous published rates. Three studies with at least 5-year follow-up in MCF patients with initially successful HP found that class A/B was maintained at 5 years in 70% (n = 16 of 23) (14), 75% (n = 12 of 16) (16), and 84% (n = 27 of 32) (17). In a review of RS patients with initially preserved class A/B hearing, 87% (n = 47 of 54) maintained A/B at a minimum of 6 years follow-up (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, with serial observation and radiation, there is uncertainty in the duration of maintaining serviceable hearing. Long-term data are slowly accumulating regarding hearing outcomes with each management approach (6–10), but outcomes beyond 5 (11–18) and 10 (18,19) years remain limited. As VS diagnoses are made at earlier time points in the tumors' natural history, long-term HP data will aid in counseling patients presenting with serviceable hearing.…”
Section: Introductionmentioning
confidence: 99%